Yahoo Web Search

1. Sort by

1. Establish the following identity: csc(theta) - cot(theta) = (sin(theta))/(1+cos(theta))?

LHS: csc θ - cot θ = 1/sin θ - cos θ/sin θ = (1 - cos θ)/sin θ Multiply...

1 Answers · Science & Mathematics · 08/11/2017

2. Prove math 10 points?

... - cos2A = 2sin(B + A)sin(A - B) LHS = [2cos(A + B)cos(A - B)] /[2sin(B + A)sin...

1 Answers · Science & Mathematics · 21/10/2017

3. How to proof this identity trigonometry?

LHS= cos(4x)+cos(6x)-cos(2x)-1= cos(4x)+cos(6x)-2cos^2(x)= 2cos(5x)cos(x)-2cos^2(x)= 2cos(x)[cos(5x)-cos(x)]= 2cos(x)[-2sin(3x)sin(2x)]= -4cos(x)sin(3x)sin(2x)= RHS

2 Answers · Science & Mathematics · 21/10/2017

4. How to solve 5/6x=-2/18 What are the steps? Please explain this example the best you can with steps to your final answer.?

5/6x=-2/18 multiply LHS by 3/3 15/18x = -2/18 multiply both sides by 18 15x = -2 divide both ...

6 Answers · Science & Mathematics · 16/10/2017

5. Prove this identity trigonometry?

... + sin B) = (sin B - sin A) / (cos A + cos B) LHS = (cosA - cosB)/(sinA + sinB) {multiply by conjugate of...

4 Answers · Science & Mathematics · 14/10/2017

6. Prove that cos 6A - 2 cos 4A - cos 2A + 2 = 32 sin⁴ A cos² A ?

...)cos(2A) and 2−2cos(4A) = 4sin²(2A) ∴ LHS = 4sin²(2A)(1−cos(2A)) = 4(4sin²Acos²A)(...

1 Answers · Science & Mathematics · 03/10/2017

7. 4ln(x)−ln(x^2)=1 solve for x?

...go sweetheart :) 4ln(x) - ln(x²) = 1 Apply the log laws on the LHS : ln(x^4) - ln(x²) = 1 ln(x²) = 1 Now take the exponential on...

2 Answers · Science & Mathematics · 29/09/2017

8. Proof of vector identity: v ⋅ ∇ v = (1/2) ∇ (v ⋅ v) - [v x [∇ x v]]?

...to show that the x components are the same on both sides LHS = (v₁∂/∂x+v₂∂/∂y+v₃∂/∂z)(v₁,v₂...

3 Answers · Science & Mathematics · 16/09/2017

9. Why is Algebra so hard?

...now, collect like terms) = (a + b)x + (2a + b). So, since the 1 on the LHS has no x coefficient, 1 = 2a + b & 0 = a + b. So b= -a, so a = 1...

2 Answers · Science & Mathematics · 13/09/2017

10. Prove that (x+y)/2 ≥√xy for any real non-negative numbers x and y. Show that equality happens if and only if x = y.?

.... What happens when x = y ?????? Substitute y = x : LHS = x + x = 2x RHS = 2√(x*x) = 2√(x²) = 2x Since LHS...

2 Answers · Science & Mathematics · 10/09/2017